2009
DOI: 10.1111/j.1532-950x.2009.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of RANK, RANKL and OPG in Healthy and Arthritic Canine Elbow Joints

Abstract: Therapeutic use of neutralizing antibodies against RANKL to inhibit osteoclast activation warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 26 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…OPG is expressed and produced by many cell types. It was reported that human chondrocytes and annulus fibrosus of IVD express OPG and RANKL [79]. However, the effect of OPG on IVDs has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…OPG is expressed and produced by many cell types. It was reported that human chondrocytes and annulus fibrosus of IVD express OPG and RANKL [79]. However, the effect of OPG on IVDs has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…33 This moderate crossreactivity in specific locations did not interfere with interpretation of results as corresponding structures were clearly distinct from the regions and tissues of interest. However, weak immunostaining of epithelial tissue, blood vessels, and dental calculus was observed.…”
Section: Resultsmentioning
confidence: 98%
“…33 Although no complete sets of serial sections were available, fullsize transverse sections enabled a comprehensive assessment of the teeth and periodontal ligament. 33 Although no complete sets of serial sections were available, fullsize transverse sections enabled a comprehensive assessment of the teeth and periodontal ligament.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations